Unhu/Ubuntu theory as the basis of administrator-teacher relationship: A grounded theory approach - Gomba, Clifford (Papanda Publisher, 2024)
The teacher’s functionality depends on the working environment he/she is operating in and, in some ways, depends on the relationship with the headmaster. The relationship may be due to, but not limited to, leadership styles, personalities, and other attributes of both the teacher and the school management system. Workplace relationships influence the performance of employees in any organization. This grounded theory study aims to get an understanding of the basic social processes in administrator-teacher relationships and come up with an explanation of that kind of relationship. Eleven (n = 11) participants in the study were all qualified teachers, teaching at the two rural-based Catholic-run schools. Data collected through interviews were audiotaped, memoed, and transcribed. The results from this study showed that teachers classified their relationship with their administrators as professional/good, complicated and bad, selective treatment, supportive and indifferent, or no relationship; and all linked to having unhu/ubuntu or lack of it. It is the recommendation of this study that administrators should be trained, and have unhu/ubuntu philosophy when dealing with their teachers and students.